Novel 1, 3, 4-oxadiazoles as antitubercular agents with limited activity against drug-resistant tuberculosis. (20th March 2019) - Makane, Vitthal B; Krishna, Vagolu Siva; Krishna, Eruva Vamshi; Shukla, Manjulika; Mahizhaveni, Balakrishnan; Misra, Sunil; Chopra, Sidharth; Sriram, Dharmarajan; Azger Dusthackeer, Vijayan N; Rode, Haridas B
Aim: In recent times, heterocyclic chemotypes are being explored for the development of new antimycobacterials that target the drug-resistant tuberculosis. Here, we are disclosing the 5-substitued 2-mercapto-1, 3, 4-oxadiazoles as potent antitubercular agents.Methodology: A small library of 2-mercapto-1, 3, 4-oxadiazoles was synthesized using various acids. The compounds were evaluated for antituberculosis activity against M. tuberculosis H37Rv.Results: Compound8j was identified as antitubercular lead with MIC of 0.6 μg/ml against M. tuberculosis H37Rv. This compound was nontoxic to CHO-K1 cells and showed selectivity index of 39. Of note, 8j showed antitubercular activity against pre-extensively drug-resistant clinical isolate of Mycobacterium with MIC of 2 μg/ml.Conclusion: This study provides potent antitubercular agent which can be further optimized to discover novel antibiotics. Graphical abstract: